Functional Abdominal Pain Patient Subtypes in Childhood Predict Functional Gastrointestinal Disorders with Chronic Pain and Psychiatric Comorbidities in Adolescence and Adulthood - Walker, Lynn S. (2012)
Although pediatric functional abdominal pain (FAP) has been linked to abdominal pain later in life, childhood predictors of long-term outcomes have not been identified. This study evaluated whether distinct FAP profiles based on patterns of pain and adaptation in childhood could be identified and whether these profiles predicted differences in clinical outcomes and central sensitization (wind-up) on average 9 years later. In 843 pediatric FAP patients, cluster analysis was used to identify subgroups at initial FAP evaluation based on profiles of pain severity, gastrointestinal (GI) and non-GI symptoms, pain threat appraisal, pain coping efficacy, catastrophizing, negative affect, and activity impairment. Three profiles were identified: High Pain Dysfunctional, High Pain Adaptive, and Low Pain Adaptive. Logistic regression analyses controlling for age and sex showed that, compared to pediatric patients with the Low Pain Adaptive profile, those with the High Pain Dysfunctional profile were significantly more likely at long-term follow-up to meet criteria for pain-related functional gastrointestinal disorder (FGID) (OR: 3.45; CI: 1.95–6.11), FGID with comorbid non-abdominal chronic pain (OR: 2.6; CI:1.45–4.66), and FGID with comorbid anxiety or depressive psychiatric disorder (OR: 2.84; CI: 1.35–6.00). Pediatric patients with the High Pain Adaptive profile had baseline pain severity comparable to the High Pain Dysfunctional profile, but had outcomes as favorable as the Low Pain Adaptive profile. In laboratory pain testing at follow-up, High Pain Dysfunctional patients exhibited significantly greater thermal wind-up than Low Pain Adaptive patients, suggesting that a subgroup of FAP patients has outcomes consistent with widespread effects of heightened central sensitization.